Life after Trafficking in Azerbaijan: Reintegration experiences of survivors - McCarthy, Lauren A. (Anti-Trafficking Review, 2018)
Assisting survivors of trafficking is considered one of the pillars of a human rights-based response Shelter, medical, psychological and legal assistance in the short term and job placement, accommodation and reunification with family and community in the long term are critical steps for helping them recover and feel in control of their lives and futures. This paper examines survivors’ experiences of trafficking and recovery in the Azerbaijani context, using questionnaire responses from 22 women who were trafficked for sexual exploitation between 2006 and 2009 and who were assisted upon their return. It finds that while Azerbaijan has been quite successful at short-term assistance, there are still significant gaps in longer-term assistance, especially with regard to job placement and family reunification. Survivors point to these gaps as significant impediments to full reintegration into society. Looking at their experiences can provide insights into improvements in assistance programmes that can be implemented in both Azerbaijan and elsewhere.